(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
The spatial variability of salt accumulation through the soil profile was studied at Latachapali union of Kalapara upazila, Patuakhali district, Bangladesh. The soil samples were collected from 30 locations covering six villages of the union: Kuakata, Malapara, Fashipara, Khajura, Mothaopara and Tajepara. Five locations were randomly selected from each village. From each location soil samples were collected from three soil depths at 0-2 cm, 2.1-4 cm and 4.1-6 cm. Electrical conductivity of top 0-2 cm soil depth was 20.49 dS/m, in 2.1-4 cm soil depth was 7.14 dS/m and in 4.1-6 cm soil depth 4.15 dS/m. The study soils were strongly acidic having pH value 4.73, 4.99 and 5.20 in 0-2, 2.1-4 and 4.1-6 cm soil depth, respectively. The highest of 8.8 Na:K ratio was found in 0-2 cm soil depth. The Na:K ratio gradually decreased with the increase of soil depth, having 6.59 in 2.1-4 cm and 5.42. in 4.1-6 cm soil depth. The results clearly reveal that the top soil is very much sensitive to salt stress. Based on the electrical conductivity and Na:K ratio the Fashipara, Kuakata and Tajepara village were found seriously affected by salinity. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 11-23, 2018